PERISTILAHAN DALAM PERAINAN RAKYAT "TIMANG" PADA MASYARAKAT MELAYU DI KECAMATAN TANGARAN KABUPATEN SAMBAS - Firmansyah, Firmansyah; Heryana, Nanang; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research focuses on terminology in the folk game "Timang" in the Malay community in Tangaran District, Sambas Regency. Researchers used descriptive methods, qualitative research forms, and used an ethnolinguistic approach that looked at the relationship between language and cultural elements in society. The analysis carried out by researchers on the data collected includes the tools and materials, performers, and processions. Analysis of the form of terms in this study are monomorphemic, polymorphemic, and phrases. In addition, this study also describes the meaning of the term in the game "timang" lexically and culturally. The terms in this research are 38 terms consisting of 14 terms of tools and materials, 7 terms of actors, and 17 terms of procession. as research data obtained from interviews and recording processes conducted by researchers. The results of the analysis of the entire data are in the form of 17 terms in the form of basic words or monomorphemes, 16 terms in the form of polymorphemes, and 5 terms in the form of phrases. These terms as a whole have lexical meanings and as many as 16 terms contain cultural meanings.